Enhancing Organizational Citizenship Behavior Through Job Satisfaction Mediation: The Role of Spiritual Beliefs, Cooperation, and organizational Justice - Lestari, Iis; Hardhienata, Soewarto; Sunaryo, Widodo (Pascasarjana Universitas KH. Abdul Chalim, 2025)
The role of Organizational Citizenship Behavior (OCB) is increasingly pivotal in enhancing the performance and effectiveness of educational institutions, yet there remains a gap in understanding how cultural values rooted in local wisdom influence OCB. This research explores the effects of spiritual beliefs, cooperative behavior, and perceptions of organizational justice on OCB, with job satisfaction positioned as a mediating factor. A mixed-method design was utilized, combining quantitative survey data and qualitative interview findings involving educators in West Java. Analytical techniques included structural equation modeling for the quantitative data and thematic analysis for the qualitative responses. The study reveals that job satisfaction plays a crucial mediating role, particularly amplifying the influence of organizational justice, which was found to be the most dominant factor impacting OCB. These outcomes highlight the importance of nurturing a work culture that emphasizes fairness, collective harmony, and internalized values to foster higher levels of job satisfaction and discretionary behavior. The findings offer practical recommendations for educational organizations to implement policies that support psychological well-being, shared values, and organizational transparency in order to optimize positive employee contributions.